2022
DOI: 10.1371/journal.pone.0276481
|View full text |Cite
|
Sign up to set email alerts
|

Low serum uromodulin levels and their association with lupus flares

Abstract: Background Only two previous studies in systemic lupus erythematosus (SLE) patients have identified that the blood concentrations of uromodulin are lower in nephritis. However, none of them had evaluated whether a low serum uromodulin adjusted by the glomerular filtration rate (sUromod/eGFR index) contributed to identify patients in risk of lupus nephritis (LN) using multivariable models. Aim Therefore, this study aimed two objectives to evaluate the association between low serum uromodulin levels and low sU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
(47 reference statements)
0
0
0
Order By: Relevance
“…In contrast to other studies [4,202], diminished serum uromodulin concentrations showed a correlation with proteinuria severity. The correlation between lower serum uromodulin levels and proteinuria intensity remained evident even after adjusting for the eGFR using the serum uromodulin/eGFR index [200]. In conclusion, low serum uromodulin levels adjusted by eGFR could potentially serve as a marker associated with renal flares in patients with SLE.…”
Section: Lupus Nephritismentioning
confidence: 82%
See 3 more Smart Citations
“…In contrast to other studies [4,202], diminished serum uromodulin concentrations showed a correlation with proteinuria severity. The correlation between lower serum uromodulin levels and proteinuria intensity remained evident even after adjusting for the eGFR using the serum uromodulin/eGFR index [200]. In conclusion, low serum uromodulin levels adjusted by eGFR could potentially serve as a marker associated with renal flares in patients with SLE.…”
Section: Lupus Nephritismentioning
confidence: 82%
“…However, in the subsequent multivariable analysis, where serum uromodulin was adjusted for eGFR, the risk of renal flare based on the rSLEDAI was found to be 2.94, independent of other variables. The risk further rose to 4.27 when a patient with a flare had a SLICC renal disease activity score ≥ 5 [200]. Scherberich et al provided further support for these findings through their analysis of patients with CKD.…”
Section: Lupus Nephritismentioning
confidence: 90%
See 2 more Smart Citations
“…Serum uromodulin was lower in patients with renal activity and may be predictive of the risk of a renal flare (12). Similarly, beta 2-microglobulin correlated with BUN, serum creatinine and 24-h urinary protein.…”
Section: Biomarkersmentioning
confidence: 86%